2022
DOI: 10.2147/copd.s338824
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea is Associated with an Increased Prevalence of Polycythemia in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Purpose Chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) are associated with polycythemia. However, there still remain unanswered questions about the relationship between overlap syndrome (OVS), where OSA and COPD coexist, and polycythemia. Here, we aimed to establish the prevalence of polycythemia in OVS patients and to explore the impact of OSA on polycythemia. Patients and Methods Patients with COPD underwent overnight polysomnography (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Erythrocytosis was found in 6.7% [95% CI 1.4-18.3] of the 45 COPD participants. The findings were similar to those of a study in China in which 886 COPD patients were assessed for erythrocytosis, with a prevalence of 6.4% [ 39 ]. However, a study carried out in Pakistan had a higher prevalence of 10.8% [ 40 ], but the study findings were higher than those observed in Egypt (2.4%) [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Erythrocytosis was found in 6.7% [95% CI 1.4-18.3] of the 45 COPD participants. The findings were similar to those of a study in China in which 886 COPD patients were assessed for erythrocytosis, with a prevalence of 6.4% [ 39 ]. However, a study carried out in Pakistan had a higher prevalence of 10.8% [ 40 ], but the study findings were higher than those observed in Egypt (2.4%) [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…A 25-year follow-up study of the general population in Copenhagen, Denmark, established a 25% and beyond absolute risk of developing COPD among continued smokers [ 37 ], with even low-rate smokers having an elevated chance of developing lung disease in the future [ 38 ]. Thus, there are no safe limits for the effect of smoking intensity on lung disease risk, making each added year a risk factor for COPD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocytosis was found in 6.7% [95% CI1.4-18.3] of the COPD participants. The study ndings were similar to those of a study in China in which 886 COPD patients were assessed for erythrocytosis, with a prevalence of 6.4%(Zeng et al, 2022). However, a study carried out in Pakistan had a higher prevalence of 10.8%(Ullah et al, 2018), but the study ndings were higher than those observed in Egypt (2.4%) (El-Korashy et al, 2012).…”
supporting
confidence: 82%
“…The prevalence of polycythemia in our study was 8 (4.32%) which is lower as compared to a similar study conducted in Nepal, 7 whereas prevalence is higher than in the study done in China. 8 This difference might be due to different races and altitudes as reported by another study. 5 Despite the presence of different criteria to define polycythemia, the prevalence of polycythemia in this study, which was 4.324%, does not match previous estimates of 5.9-18.1%.…”
Section: Discussionmentioning
confidence: 82%